EVALUATION OF PHARMACOLOGICAL POSTCONDITIONING BY ARGININE/LEVOCARNITINE IN PATIENTS WITH STEMI/NSTEMI - Fedorchenko, M.V. (World of Medicine and Biology, 2019)
The aim of the research was to study the effect of the pharmacological postconditioning by the combined drug consisting of arginine hydrochloride and levocarnitine and its echocardiographic evaluation. In addition the standard treatment scheme of arginine/levocarnitine does not influence on the myocardial remodeling (dynamics to the eccentric myocardial hypertrophy/remodeling). Meanwhile, the myocardial reserve index credibly increases by 4%. Confirmation of the non-sufficient positive influence of the researched drug on the processes of remodeling, hypertrophy and contractility is the WMSI dynamics: from 1.74±0.07 before treatment to 1.70±0.05 (ВР=0.70 [95% ДІ 0.47-1.04; р=0.66]). Still, the LVEF increased by 4.4% (by Teicholz).